ALIH KODE DAN CAMPUR KODE BAHASA JAWA DALAM PENGAJIAN SELAPANAN DUSUN GEDANGAN DESA NGARGOSOKA - Novi Wiji Lestari; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to describe the form of code switching and mixed language code, the function of code switching and Javanese language code mixing, and the factors behind code switching and Javanese language code mixing in the recitation of the Selapanan Gedangan Hamlet, Ngargosoka Village. This type of research is qualitative descriptive research. The research data is in the form of a unit of events in the form of sentences or paragraphs which contain code switching and code mixing. The data source of this research is the use of language in the selapanan recitation of Gedangan hamlet, Ngargosoka village. The instruments in this study were researchers who were provided with a set of knowledge related to the form of code switching and code mixing. The method of data collection uses reading techniques and note taking techniques. The data analysis method used is the refer method. The data analysis technique uses matching techniques that are realized by basic techniques. The basic technique used in this study is the determining element (PUP) technique. The results of this study indicate that the form of Javanese code switching in the recitation of the Selapanan of Gedangan hamlet in Ngargosoka village was divided into three, namely: a) code switching from the Javanese language into a variety of Krama in Indonesian, b) code switching from Javanese to various types of ngoko , c) code switching from Javanese in the form of ngoko into Javanese in a variety of manners. The function of Javanese code switching in the recitation of the Selapanan of Gedangan hamlet in Ngargosoka village is as follows: a) more persuasive to invite or order, b) more argumentative, c) more communicative. The factors behind the Javanese language code switching in the Selapanan Gedangan hamlet in Ngargosoka village are: a) speakers, b) politeness and politeness, c) the subject matter (topic), d) versus speech, e) to generate a sense of humor, f) to just prestigious. Mixing the Javanese language code in the recitation of the Selapanan Gedangan hamlet, Ngargosoka village is divided into two forms, namely: a) basic word forms, and b) repetitive word forms. The function of interfering with the Javanese language code in the recitation of the Selapanan in the Gedangan hamlet of Ngargosoka village is as follows. a) more argumentative, b) more communicative, and c) more prestigious or prestigious. The factors behind the Javanese language code mix in the recitation of the Selapanan in Gedangan hamlet, Ngargosoka village are: a) politeness, and b) explain and interpret.